Does aerobic exercise improve or impair cardiorespiratory fitness and health among cleaners? A cluster randomized controlled trial - Korshøj, Mette; Lidegaard, Mark; Skotte, Jørgen H.; Krustrup, Peter; Krause, Niklas; Søgaard, Karen; Holtermann, Andreas (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVE ': 'It is unknown if aerobic exercise overloads or improves the cardiovascular system among workers with high occupational physical activity. This was investigated in a worksite randomized controlled trial (RCT) of aerobic exercise among cleaners. ' ' METHODS ': 'We randomized 116 cleaners between 18–65 years. The aerobic exercise group (N=57) performed worksite aerobic exercise (30 minutes twice a week) and the reference group (N=59) received lectures. Cardiorespiratory fitness, blood pressure (BP) and diurnal heart rate (HR) for measuring aerobic workload [% HR reserve (% HRR)] were collected at baseline and after four months. A repeated measure 2×2 multi-adjusted mixed-model design was applied to compare the between-group differences in an intention-to-treat analysis. ' ' RESULTS ': 'Between-group differences (P<0.01) were found: cardiorespiratory fitness 2.2 [standard error (SE) 0.8] ml O 2 × min -1 × kg -1 [95% confidence interval (95% CI) 0.6–3.8], aerobic workload - 3.5 (SE 1.2) % HRR (95% CI - 5.9– -1.0), resting HR -3.8 (SE 1.2) bpm (95 % CI -6.1– - 1.4), sleeping HR -3.8 (SE 1.1) bpm (95% CI - 5.9– - 1.7), and systolic BP 3.6 (SE 1.3) mmHg (95% CI 1.1–6.0). ' ' CONCLUSIONS ': 'Worksite aerobic exercise seems to improve cardiorespiratory fitness, aerobic workload, and resting and sleeping HR, but increase systolic BP among cleaners. Beneficial physiological cardiovascular effects are seen from aerobic exercise, but also a harmful effect is evident. Therefore, recommendations should take into consideration the potential cardiovascular overload from additional aerobic exercise on workers with high levels of occupational physical activity.
Keywords: Actiheart; aerobic exercise; aerobic training; aerobic workload; blood pressure; cardiorespiratory fitness; cleaner; cluster randomized controlled trial; Denmark; physical activity; physical work demand; RCT; resting heart rate; sleeping heart rate; step test; work demand; worksite intervention